Effect of Severe Vitamin D Deficiency at Admission on Shock Reversal in Children With Septic Shock: A Prospective Observational Study. (May 2019) - Sankar, Jhuma; Ismail, Javed; Das, Rashmi; Dev, Nishanth; Chitkara, Anubhuti; Sankar, M. Jeeva
Objectives: To evaluate the association of severe vitamin D deficiency with clinically important outcomes in children with septic shock. Methods: We enrolled children ≤17 years with septic shock prospectively over a period of 6 months. We estimated 25-hydroxyvitamin D [25 (OH) D] levels at admission and 72 hours. Severe deficiency was defined as serum 25 (OH) <10 ng/mL. We performed univariate and multivariate analysis to evaluate association with clinically important outcomes. Results: Forty-three children were enrolled in the study. The prevalence of severe vitamin D deficiency was 72% and 69% at admission and 72 hours, respectively. On univariate analysis, severe vitamin D deficiency at admission was associated with lower rates of shock reversal, 74% (23) versus 25% (3); relative risk (95% confidence interval [CI]): 2.9 (1.09-8.08), at 24 hours and greater need for fluid boluses (75 vs 59 mL/kg). On multivariate analysis, nonresolution of shock at 24 hours was significantly associated with severe vitamin D deficiency after adjusting for other key baseline and clinical variables, adjusted odds ratio (95% CI): 12 (2.01-87.01); 0.01. Conclusion: The prevalence of severe vitamin D deficiency is high in children with septic shock admitted to pediatric intensive care unit. Severe vitamin D deficiency at admission seems to be associated with lower rates of shock reversal at 24 hours of ICU stay. Our study provides preliminary data for planning interventional studies in children with septic shock and severe vitamin D deficiency.